“Itinerary I – Travellers’ memories of the Alentejo”, in Merchants, Routes and Trade in the Mediterranean – Memoirs of travel and travellers: Looking for landmarks and watching new and ancient landscapes, - Fialho Conde, Antónia (2012)
Diverse perspectives of the South of Portugal from de regard of european travelers since the roman period.